Absorption Methanyl Yellow Dye Using Hydrogel of Cassava Peel Starch (Manihot esculenta Cranzt) - Firnanelty, Firnanelty (ALKIMIA, 2021)
Hydrogel of cassava peel starch was successfully decreased methanyl yellow dye. This adsorbent was employed to adsorb typical organic cationic dye contaminants from high concentration effluents. This study aimed to determine characteristic of cassava peel starch hydrogel and ability of hydrogel increased dyes. The stages of hydrogel consist of extracting cassava peel starch, making a starch solution, making hydrogel, testing water absorption, and analysing with FTIR and UV-Vis spectrophotometer. The results have obtained that the cassava peel starch hydrogel had have N-H group. Result of hydrogel had been contacted with dyes that showed N=N and S=O groups from the initial functional groups of cassava peel starch in FTIR spectum. The highest absorption of hydrogel was at 30 ppm methanyl yellow dye concentration, which was 31.72%. This result showed that the hydrogel of cassava peel starch can be used as an absorbent of methanyl yellow dye.